2019
DOI: 10.3762/bjoc.15.90
|View full text |Cite
|
Sign up to set email alerts
|

Towards the preparation of synthetic outer membrane vesicle models with micromolar affinity to wheat germ agglutinin using a dialkyl thioglycoside

Abstract: A series of alkyl thioglycosides and alkyl thiodiglycosides bearing glucose and N-acetylglucosamine residues were prepared by thiol–ene coupling in moderate to good yields (40–85%). Their binding ability towards wheat germ agglutinin was measured by competitive enzyme-linked lectin assays. One of the synthetic compounds presenting two GlcNAc units showed the highest inhibitory effect of this study with an IC50 of 11 µM corresponding to a 3182-fold improvement compared to GlcNAc. These synthetic molecules were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…Sugar-based surfactants are widely considered mild detergents and have been commonly used as solubilizing and non-denaturing detergents for MP applications including n-octyl-β-D-glucoside (OG), [2][3] n-decyl-β-D-maltoside (DM), 2 n-dodecyl-β-D-maltoside (DDM), [4][5][6] lactobionamides, 7 and thioglycoside such as n-octyl-β-D-thioglucopyranoside (OTG). [8][9] Recently, some sugar-based surfactants with branched polar headgroups or branched hydrophobic tails have been described for the same objective, namely, alkyl diglucosides (DigluM), 10 CALX-173-GK, 11 and laurylmaltose neopentylglycol (LMNG). [12][13][14] Fluorinated surfactants (FSs) bear several perfluorinated carbon atoms in their hydrophobic tail.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sugar-based surfactants are widely considered mild detergents and have been commonly used as solubilizing and non-denaturing detergents for MP applications including n-octyl-β-D-glucoside (OG), [2][3] n-decyl-β-D-maltoside (DM), 2 n-dodecyl-β-D-maltoside (DDM), [4][5][6] lactobionamides, 7 and thioglycoside such as n-octyl-β-D-thioglucopyranoside (OTG). [8][9] Recently, some sugar-based surfactants with branched polar headgroups or branched hydrophobic tails have been described for the same objective, namely, alkyl diglucosides (DigluM), 10 CALX-173-GK, 11 and laurylmaltose neopentylglycol (LMNG). [12][13][14] Fluorinated surfactants (FSs) bear several perfluorinated carbon atoms in their hydrophobic tail.…”
Section: Introductionmentioning
confidence: 99%
“…MPs are usually extracted from native membrane bilayers using a detergent that, ideally, should combine both solubilizing and stabilizing properties so as to preserve the native structures of MPs in non-native environments. Sugar-based surfactants are widely considered to be mild detergents and have been commonly used as solubilizing and non-denaturing detergents for MP applications including n -octyl-β-D-glucoside (OG), , n -decyl-β-D-maltoside (DM), n -dodecyl-β-D-maltoside (DDM), lactobionamides, and thioglycoside such as n -octyl-β-D-thioglucopyranoside (OTG). , Recently, some sugar-based surfactants with branched polar headgroups or branched hydrophobic tails have been described for the same objective, namely, alkyl diglucosides (DigluM), CALX-173-GK, and laurylmaltose neopentylglycol (LMNG). …”
Section: Introductionmentioning
confidence: 99%
“…[19] To solve these drawbacks we hypothesized that synthetic OMVs (S-OMVs), composed of mixtures of "onpurpose" prepared glycolipids and non-toxic and non-immunogenic phospholipids in variable compositions could be good candidates for different uses such as synthetic vaccines or vaccine carriers (Figure 1). [20] Among a series of synthetic candidates, glycolipids seem to be an optimum choice for their amphiphilic properties [21] and Nalkyl-thio-glycosides (TGL) are the more attractive ones. In fact, they are known for their co-surfactant abilities, [22] presenting interesting antimicrobial activities, [23] acting as glycosidase inhibitors, and being resistant towards glycoside hydrolases.…”
Section: Introductionmentioning
confidence: 99%
“…In principle, each glycolipid can be prepared in good amounts (hundreds of milligrams) and purified through silica column chromatography reducing time and purification costs. [21] Mixtures of glycolipids and naturally occurring phospholipids can be assembled in the form of vesicles by well-known methodologies [37] and purified by simple filtration upon reduced pressure, if necessary. [38] Furthermore, this assembly naturally enhances the multivalence depending on the concentration of the glycolipid used and avoids any clustering effect (Figure 1b).…”
Section: Introductionmentioning
confidence: 99%
“…Rademacher et al reported the delivery of vaccines to dermal Langerhans cells using a targeted liposome decorated with a glycomimetic ligand for binding to their surface receptor Langerin 22 . Additionally, the opportunity to use carbohydrate-decorated liposomes as vaccines against infections and cancer have been extensively studied in the last decade [23][24][25][26] . The high potency and efficacy of the liposomes functionalized with carbohydrate moieties in inhibiting corresponding lectins is provided by their multivalent interaction with the proteins, similar to those observed for other multivalent systems 27 .…”
Section: Introductionmentioning
confidence: 99%